"I'm not religious, but Tito is a God": Tito, Kumrovec, and the New Pilgrims - Belaj, Marijana (2008)
Although there can be no doubt that Tito was turned into a kind of instrument of communist rule after he died, he has also retaind an important place in the private spheres of life for many individuals. A lively and non-institutional venerations of Tito after his death can be seen in occasional actions of citizens of former Yugoslavia. Expressions of direct and personal attachment to Tito give an especially vivid account of his life after death, usually reffering to communication with him and the need to bring him closer and make him more familiar. In the Croatian village of Kumrovec, where in addition to the usual traditional buildings in the open-air museum, the house where the former Yugoslavian president Josip Broz Tito was born and a statue of the man are situated. The area around his statue is seen as a stage on which conflicts between different collective memories take place, especially during the annual celebration of the Day of Youth in Kumrovec. While it was not organizer´s intention to create a personality cult, for participants, who come there in order to make close contact with the Josip Broz, the statue of Tito invites special gestures, action and emotions which are not simply suggestive of the religious, but are in fact taken from religious practice - expressions of experience of Tito´s statue are similar to forms of religiosity found in the worshipping of saints. The site is thus converted into pilgrimage place, at least on this one day of the year.
ENG